PKM PENINGKATAN KAPASITAS DESAWISATA DI DESA GALENGDOWO KECAMATAN WONOSALAM KABUPATEN JOMBANG - Sayekti Suindyah Dwiningwarni; Mei Indrawati; Machrus Ali; Syamsiyah Yuli Dwi Andari (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Galengdowo Village, Wonosalam District, Jombang Regency which has good tourism potential, but is still not managed optimally. The partner of this partnership program is Pokdarwis Argo Wayang which is one of the business units of BUMDESA Lohjinawi Galengdowo Village. During the COVID-19 pandemic, and the enactment of regulations regarding PSBB, Emergency PPKM and PPKM Levels 1-4, caused tourist attractions in this village to be completely closed. The closure of this tourist attraction has an impact on decreasing the number of tourist visits to tourist sites even to zero (no visitors), so that it does not generate income for either the village or the community. The objectives of this program are 1) Increasing the capacity of village tourism during the covid-19 pandemic, 2) Increasing the promotion of village tourism through the website, 3) making completeness of village tourism. The methods used are 1) website design, database and promotion design, 2) website training and assistance, database and promotion design, 3) tourism management training, tour guides and organizations. The results of this partnership program include 1) optimizing tourism objects by making directions to tourist sites, 2) optimizing the tourism information center office with the inauguration of the tourism information center office, 3) increasing Pokdarwis awareness and supporting facilities for village tourism promotion available, 4) managerial improvement and skills of Pokdarwis management.